MANAJEMEN STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PENDIDIKAN KARAKTER ISLAM - RIFDILLAH, MUHAMMAD; SAPPAYANI, SHALIMA; TARIHORAN, NAF’AN; NUGRAHA, ENUNG (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research discusses the elements that influence the strategic management of school principals in improving Islamic character education, by involving the roles of various parties, both external and internal. To identify aspects of strategic management that support the formation of student character, a synthesis was carried out using the PRISMA method based on the keywords